Bacteriostatic and Bactericidal Activities of Various Antibiotics Against Bacteroides fragilis - Zabransky, R. J. (1973)
The minimal inhibitory concentrations and minimal bactericidal concentrations of seven antibiotics were determined by broth dilution tests for 50 clinical isolates of Bacteroides fragilis. Chloramphenicol, erythromycin, lincomycin, clindamycin, and rifampin inhibited 80 to 100% of the strains at concentrations attainable in the serum. Penicillin and tetracycline were less effective, inhibiting 4 and 40% of the strains, respectively, at concentrations attainable in the serum. The strains exhibited a bimodal distribution with tetracycline but a very narrow pattern of susceptibility with chloramphenicol. Bactericidal concentrations were 4- to 128- fold higher than minimal inhibitory concentrations for all antibiotics; only clindamycin showed bactericidal activity at levels attainable in serum. Clindamycin was significantly more effective than lincomycin as determined by tests of inhibitory and bactericidal activity. The distinct patterns of susceptibility of B. fragilis may be used for the preliminary selection of antimicrobial therapy.